BENTUK POLA PUKULAN KELUHKUPAN PADA MASYARAKAT SUKU DAYA MUARADUA OKU SELATAN - Adoma, Auzi Madona (Besaung : Jurnal Seni Desain dan Budaya)
Keluhkupan is a traditional tool used by the Daya tribe as the conveyor of information by using the main wood (keluhkupan) and stick (helu) which are hit with hard blows that have different rhythmic patterns from the signs of disaster that exist in each wasp of complaints. among them are fatalities, natural disasters and riots. The three strokes have different sound patterns from dynamics, tempo and rhythm. The people who are believed to beat Keluhkupan are only allowed to be traditional leaders (men only) and those who beat Keluhkupan must really know how the sound patterns of Negu Death, Negu Sasah Bencana and Negu Sasah Huru-hara sound patterns. Negu Death is carried out when a villager dies, traditional leaders beat Keluhkupan from soft to stronger with punches from slowly to faster. Negu Sasah This wasp disaster is carried out if there is a disaster tokah adat hitting Keluhkupan powerfully and quickly. Negu Sasah This wasp riot is a sign that there has been a fight between the traditional leaders hitting Keluhkupan quickly and strongly, indicating haste or Kesasah.